Efficacy, safety and pharmacokinetics of a new high‐purity factor X concentrate in subjects with hereditary factor X deficiency. (8th March 2016) - Austin, S. K.; Kavakli, K.; Norton, M.; Peyvandi, F.; Shapiro, A.; ,
Abstract : Introduction: Hereditary factor X (FX) deficiency is a rare bleeding disorder affecting 1:500 000 to 1:1 000 000 of individuals. Until recently, no specific replacement factor concentrate was available. Aim: The aim of this study was to assess safety and efficacy of a new, high‐purity plasma‐derived FX concentrate (pdFX) in subjects with hereditary FX deficiency. Methods: Subjects aged ≥12 years with moderate or severe FX deficiency (plasma FX activity <5 IU dL −1 ) received 25 IU kg −1 pdFX as on‐demand treatment or short‐term prophylaxis for 6 months to 2 years. Subjects assessed pdFX efficacy for each bleed; at end‐of‐study, investigators assessed overall pdFX efficacy. Blood samples for pharmacokinetic analysis were obtained at baseline and ≥6 months. Safety was assessed by adverse events (AEs), inhibitor development and changes in laboratory parameters. Results: Sixteen enrolled subjects (six aged 12–17 years; 10 aged 18–58 years) received a total of 468 pdFX infusions. In the 187 analysed bleeds, pdFX efficacy was categorized as excellent, good, poor or unassessable in 90.9%, 7.5%, 1.1% and 0.5% of bleeds respectively; 83% of bleeds were treated with one infusion. For pdFX, mean (median; interquartile range) incremental recovery and half‐life were 2.00 (2.12; 1.79–2.37) IU dL −1 per IU kg −1 and 29.4 (28.6; 25.8–33.1) h respectively. No serious AEs possibly related to pdFX or evidence of FX inhibitors were observed, and no hypersensitivity reactions or clinically significant trends were detected in laboratory parameters. Conclusion: These results demonstrate that a dose of 25 IU kg −1 pdFX is safe and efficacious for on‐demand treatment and short‐term prophylaxis in subjects with moderate or severe hereditary FX deficiency.